POLA KOMUNIKASI DAKWAH PIMPINAN DAERAH MUHAMADIYAH OGAN ILIR DALAM BERDAKWAH TERGADAP MASYARAKAT - Muksin Muksin; Yenrizal Yenrizal; K.A Bukhori (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2021)
In this research, it discusses how the communication patterns of the Muhammadiyah Regional Leaders in developing the da'wah activities carried out in Ogan Ilir Regency. In this research, it is hoped that it can provide benefits and a reference for the Regional Leadership of Muhammadiyah Ogan Ilr in carrying out da'wah activities in the community. The method used in this research is descriptive qualitative, that is, the researcher takes the data by interviewing local leaders. branches, twigs and da'i in Muhammadiyah Ogan Ilir. Many patterns were developed in preaching. The preaching developed by the Regional Leadership of Muhammadiyah Ogan Ilir shows that the dakwah patterns applied are oral and verbal dakwah, the two communication patterns of oral and verbal dakwah communication which are more effectively implemented by the Regional Leadership of Muhammadiyah Ogan Ilir.